Development, liberalisation and government - Gill, S.S. (2004)
This article aims at correcting the popular perspective that spectacular growth in some emerging areas has been achieved owing to deregulation and liberalisation regime. The strides made in the IT sector that have made India a superpower in the software technology have resulted from a sustained policy and legislative intervention. Application of information technology in governance is another phenomenon that highlights efforts aimed at making administration more efficient and citizen-focused. It emphasises the crucial role of government in ensuring that fruits of development, economic as well as technological, reach deep down the society. - Reproduced.
Keywords: Good governance; Liberalization; Information technology